Limnological characteristics of the Amazonic Cashibococha Lake (UcayaliPeru) at 2001 - Riofrío, José (2003)
Cashibococha lagoon was studied during 2001 year. Three stations were bimonthly sampling. Cashibococha have greenish to brownish colour water, pH between 6 to 6,8, Conductivity 10 to 30 µS.cm-1 , Transparency 21 to 59 cm and Total Alkalinity 14 to 22 mg CaCO3 / L. Surface temperature were between 24,4 and 37° C and Dissolved Oxygen 1,3 and 7,4 mg / L. Bacteriological analysis report 350 to 3600 CFU / mL for mesophilic aerobic bacteria and 3 to 43 NMP / 100 mL for total Coliforms. A total of 47 species of Freshwater Macrophytes were recorded and mayor diversity was associated with inundation of the forest period (octubre − noviembre). A total of 52 phytoplankton species were found, Chlorophyta Division was the dominant and Actinastrum hantzschi, Spirogyra sp., Eudorina elegans, Pandorina morum y Closterium kuetzingui were the principal species. In zooplankton community was recorded 54 species and the taxa dominant was Rotifera with Brachionus patulus macracanthus and Polyarthra vulgaris as principal species. Characiforms fishes was dominant and Curimata vittata the principal specie. Shannon-Wiener diversity index were highest to 3,0 bits. ind-1 in all places and times of sampling.